Code Mixing Analysis Found in Aplaus Magazine - Syahrul Efendi Lubis (ITScience (Information Technology and Science), 2021)
Abstract This study deals with code-mixing in Aplaus magazine. The objective of the study is to analyze the components of language used in code-mixing namely word and phrase, then to find out the components of language which occurs dominantly in code-mixing in Aplaus magazine. This study is limited on the use of code-mixing only in English and Indonesian language in articles of Aplaus magazine and it taken randomly as the sample. The study was conducted by using descriptive quantitative design. The technique for collecting the data was a documentary technique. The data were analyzed based on the components of language which consists of word and phrase. Having analyzed the data, it is found that the components of language dominantly used is in word. Noun consists of 56 in the class of word, 5 for verbs, 4 for Adverbs, 2 for Adjectives, and 1 for interjection, while if it is seen from the class of word in phrase; 16 for noun phrases, 13 for adjective phrases, 2 for adverb phrases and the last 1 for prepositional phrase.